Physical properties of shallow ice cores from Antarctic and sub-Antarctic islands - Thomas, Elizabeth Ruth; Gacitua, Guisella; Pedro, Joel B.; King, Amy Constance Faith; Markle, Bradley; Potocki, Mariusz; Moser, Dorothea Elisabeth (My University, 2021)
The sub-Antarctic is one of the most data-sparse regions on earth. A number of glaciated Antarctic and sub-Antarctic islands have the potential to provide unique ice core records of past climate, atmospheric circulation, and sea ice. However, very little is known about the glaciology of these remote islands or their vulnerability to warming atmospheric temperature. Here we present melt histories and density profiles from shallow ice (firn) cores (14 to 24 m) drilled on three sub-Antarctic islands and two Antarctic coastal domes. Additionally, complementary ground-penetrating radar (GPR) data were collected to further characterize each site and assess the spatial distribution of the observed melt layers. This study includes the first ever firn cores from Bouvet Island (54 degrees 25'19 '' S, 03 degrees 23'27 '' E) in the South Atlantic, from Peter I Island (68 degrees 51'05 '' 5, 90 degrees 30'35 '' W) in the Bellingshausen Sea, and from Young Island (66 degrees 31'44 '' S, 162 degrees 33'21 '' E) in the Ross Sea sector's Balleny island chain. Despite their sub-Antarctic location, surface melt is low at most sites (melt layers account for similar to 10 % of total core), with undisturbed ice layers in the upper similar to 40 m, suggesting minimal impact of meltwater percolation. The exception is Young Island, where melt layers account for 47 % of the firn core. Surface snow densities range from 0.47 to 0.52 kg m(-3), with close-off depths ranging from 21 to 51 m. Based on the measured density, we estimate that the bottom ages of a 100 m ice core drilled on Peter 1 Island would reach similar to 1856 CE and similar to 1874 CE at Young Island.
Keywords: Firn; Meltwater; Antarctic ice sheet; Ice core